Kesuksesan BTS Meal: Peran Kolaborasi Atau Media Sosial? (Studi Pada Konsumen Mcdonald’s di Malang) - Mauristania Hasman; Kartika Anggraeni Sudiono Putri (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study was to determine the simultaneous and partial effect of co-branding and pemasaran media sosial on purchasing decisions. This research method uses a quantitative approach. Data were obtained from survey techniques by distributing questionnaires via the Google form link. The number of samples used is 150 BTS Meal respondents in Malang City, with purposive sampling technique. The analytical method used is multiple linear regression analysis using the SPSS application. The results of the study partially show that there is a significant positive effect of co-branding and pemasaran media sosial on purchasing decisions on BTS Meal products. The results of the study simultaneously show that there is a significant positive effect of co-branding and pemasaran media sosial on purchasing decisions for McDonald's BTS Meal products.